2020
DOI: 10.1101/2020.08.27.270272
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibiotic tolerance is associated with a broad and complex transcriptional response inE. coli

Abstract: In a given bacterial population, antibiotic treatment will kill a large portion of the population, while a small, tolerant subpopulation will survive. Tolerant cells disrupt the efficacy of antibiotic treatment and increase the likelihood that a population gains antibiotic resistance. When a population becomes resistant, antibiotic treatment fails, which is a major health concern. Since antibiotic tolerance often leads to resistance, we have taken a systems biology approach to examine how transcriptional netwo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 112 publications
(198 reference statements)
0
10
0
Order By: Relevance
“…This is due to the mismatch between the cell’s relatively low number of proteases and the high number of proteins (table 1). Proteolytic queueing has been observed in wild-type bacteria during stress conditions and linked to up-regulation of the sigma factors σ S and σ 32 [24,174177]. It is also associated with antibiotic survival strategies [177,178].…”
Section: Synthetic Oscillators and Degradation Bottlenecksmentioning
confidence: 99%
“…This is due to the mismatch between the cell’s relatively low number of proteases and the high number of proteins (table 1). Proteolytic queueing has been observed in wild-type bacteria during stress conditions and linked to up-regulation of the sigma factors σ S and σ 32 [24,174177]. It is also associated with antibiotic survival strategies [177,178].…”
Section: Synthetic Oscillators and Degradation Bottlenecksmentioning
confidence: 99%
“…It has been shown that global regulators (9)(10)(11)(12), DNA supercoiling (13) and small RNAs (14), among other, can select large cohorts of stress-specific, responsive genes. It was also reported that 60%-90% of E. coli genes respond to changing growth conditions following a constant global scaling factor (15).…”
Section: Introductionmentioning
confidence: 99%
“…In our recent work, we demonstrate that antibiotic tolerance in Escherichia coli is a whole-cell response and can occur through multiple pathways or networks, which may work simultaneously and cooperatively to survive against antibiotics (Deter et al, 2020). Our strategy to study the underlying mechanisms of persistence was to use a bacterial species that contains mainly essential genes and networks with reduced complexity and fewer networks.…”
Section: Introductionmentioning
confidence: 99%
“…This result is also coherent with our recently published data, which established that interfering with protein degradation by forming a proteolytic queue at ClpXP will increase tolerance levels dramatically (Deter et al, 2019a). Transcriptomic analysis of queuing-tolerant population showed upregulation of genes related to metabolism and energy (Deter et al, 2020b). However, other studies reported that ppGpp and ATP reduction are not essential for persistence (Bhaskar et al, 2018; Chowdhury et al, 2016; Pontes and Groisman, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation